Mercado imobili?rio e a import?ncia das caracter?sticas locais: uma modelagem de precifica??o hed?nica dos im?veis residenciais da cidade de Feira de Santana-BA - Sampaio, Diane de Oliveira (2023)
The objective of this study was to analyze of the residential real estate market in the city of Feira de Santana, with a focus on the utilization of hedonic pricing models. To achieve this goal, the research is based on Lancaster's attribute theory, as well as the hedonic and submarket equilibrium models proposed by Rosen. These theoretical frameworks allows to analyse the relative importance of different sets of attributes that influence the properties prices. To conduct the analysis, a detailed survey was conducted using specific advertisements for residential properties in Feira de Santana. This allowed for the definition of hedonic variables, both explanatory and dependent, to be included in the multiple regression models, focusing on the perspective of real estate supply. The results obtained from the application of the hedonic pricing models revealed unique characteristics about the residential real estate market in Feira de Santana, such as preferences for house-type properties over apartments. Among the intrinsic features of the properties, it was highlighted that the number of suites in the residence holds slightly greater relevance compared to other variables. Additionally, urban expansion and urban perimeter realignment policies also exerted influence on property valorization areas, which means that the expectations of economic agents regarding the real estate appreciation in these regions anticipated this phenomenon, as clearly observed in the SIM neighborhood. This analysis offers insights to understand which specific characteristics are most valued by buyers and how they impact the socio-economic dynamics of the city.